Geochemical background concentrations of potentially toxic elements in soils of the Caraj?s Mineral Province, southeast of the Amazonian Craton - Lima, Mauricio Wilians de (Springer Verlag, 2020)
The objective of this study was to establish background concentrations of potentially toxic elements (PTEs) in soils from the Caraj?s Mineral Province (CMP), southeastern Amazonian Craton. The PTEs Al, Ba, Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb, Ti, V, and Zn were digested in microwaves and quantified by optical emission spectrometry (ICP OES). The variability of physical-chemical and mineralogical attributes contributed to variation in PTE concentrations. High background concentrations of Al, Fe, Cr, Mn, Mo, Ni, Ti, and V and, in particular, the PTE concentrations of Cd, Cu, Cr, Ba, and Co were greater than the prevention values defined by the Brazilian National Council of Environment. Soil quality reference values (QRVs) were greater than those determined for most Brazilian states and soils in the state of Par?. The high background concentrations and QRVs of PTEs show that the region is strongly influenced by the source material, rich in ferruginous deposits and other associated minerals. The results are an important tool for establishing soil quality standards and public policies for environmental protection in regions naturally PTE enriched.